Effect of sodium hypochlorite, chlorhexidin and EDTA on dentin microhardness - Bakr, Diyar Khalid; Saleem, Sazan Sherdil; Amin, Basam Kareem (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: The use of chemical irrigants solution in root canal therapy is capable of altering the proportion of organic and inorganic components of root canals. The structural properties of dentin may be changed such as permeability, solubility and microhardness. The aim of this study was to evaluate the effects of root canal irrigants on the microhardness of root canal by using three types of irrigant solutions with different concentration and normal saline used as control group. Methods: Root halves were prepared by longitudinal splitting of the roots of 56 freshly extracted caries free maxillary second premolars and embedded in autopolymerizing acrylic resin, leaving the dentin surface exposed. The root halves were randomly divided to seven groups composed of 16 samples each and treated for five minutes with one of the following irrigants: normal saline (control group), 0.2 % chlorhexidin, 2% chlorhexidin, 2.5% sodium hypochlorite, 5.25%, 5% Ethylene dimetha tetra hydrate EDTA and 17% EDTA. After surface treatment, the dentin microhardness of the root samples were recorded at the mid-root level by using a vicker microhardness tester. The data were statistically analyzed by using one-way analysis of variance, followed by Duncans test with a significant difference test at P ≤0.05. Results: EDTA, sodium hypochlorite, and 2% chlorhexidin significantly decreased the microhardness of root dentin compared with controls (P <0.05), while 0.2% chlorhexidin had no significant effect on the microhardness of root dentin. Conclusion: The irrigant solutions affect the microhardness of the samples except 0.2%.